The Intellectual Legacy of Sheikh Nawawi al-Bantani and Sheikh Mahfudz at-Tarmasi: Contributions to Islamic Education and Modern Contexts in Indonesia - Firdaus, Syarif; Imawan, Dzulkifli Hadi (Program Studi Aqidah dan Filsafat Islam, 2024)
This study explores the intellectual contributions of two prominent Nusantara scholars, Sheikh Nawawi al-Bantani (1813–1897) and Sheikh Mahfudz at-Tarmasi (1868–1919), to the advancement of Islamic intellectualism in Indonesia. Employing a qualitative approach and a descriptive-analytical method rooted in library research, the study examines the primary works of these scholars alongside relevant secondary sources. The findings reveal that both scholars made significant contributions to various fields of Islamic studies, including Quranic exegesis, hadith, Islamic jurisprudence, and mysticism. Sheikh Nawawi al-Bantani is renowned for his systematic and practical approach, while Sheikh Mahfudz at-Tarmasi is recognized for his focus on methodological and theoretical dimensions. Their works have become essential references in Islamic boarding school education and have shaped the distinctive character of Islamic learning in Indonesia. Furthermore, this study highlights the enduring relevance of their intellectual legacies in addressing contemporary challenges and fostering the development of Islamic education. Their contributions have established a foundation for the cultivation of moderate and adaptive Islamic traditions in Indonesia, while providing a robust methodological basis for Islamic studies.